DAMPAK GLOBALISASI TERHADAP IDENTITAS KEAGAMAAN MUSLIM.PERSPEKTIF SOSIAL DAN BUDAYA DI DESA PA’BATANGANG - Nurqadriani, Nurqadriani (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study examines the impact of globalization on Muslim religious identity from social and cultural perspectives. Globalization, characterized by the rapid cross-border exchange of culture, information, and values, presents both opportunities and challenges for Muslims in interpreting, expressing, and maintaining their religious identity. Employing a descriptive qualitative approach, data were collected through observation, literature review, and in-depth interviews with religious leaders, academics, and Muslim communities. The findings reveal two contrasting sides: on the one hand, globalization broadens religious horizons and strengthens transnational solidarity through digital media, while on the other, it fosters value shifts, consumerist lifestyles, and identity crises, particularly among Muslim youth. These results highlight the need for the revitalization of religious education and the contextualization of Islamic values to remain relevant in contemporary times. The study recommends an integrative approach that combines local wisdom with global perspectives to strengthen and sustain a resilient and adaptive Muslim religious identity in the era of globalization.